البحث في الإنحراف عن النموذج المعياري من خلال دراسة التبعثر المرن للنيوترينو الإلكتروني ( النيوترينو الإلكتروني المضاد) الكتلوي على الإلكترون (Latakia University Journal -Basic Sciences Series, 2014)
تم في هذا البحث حساب  المقاطع العرضية التفاضلية  للتبعثر المرن للنيوترينو الإلكتروني (للنيوترينو الإلكتروني المضاد) على الإلكترون داخل إطار النموذج المعياري (القياسي) لفيزياء الجسيمات الأولية وخارجه . تم أيضا حساب العلاقة الرياضية المستخدمة  في دراسة الانحراف عن النموذج المعياري. بيًنت الدراسة أن هناك انحرافاً عن النموذج المعياري من المرتبة  لصنف النيوترينو الإلكتروني . لم يتمكن المرجع [16] من إظهاره بشكل واضح و مستقل  بل أظهر الانحراف بشكل وسطي لكل أصناف النيوترينو مجتمعة ، ونظراً لصغر هذا الانحراف يمكن إهماله وبالتالي لا حاجة  لتوسيع إطار النموذج المعياري ليشمل النيوترينو الإلكتروني الكتلي فهو  في هذه الحالة يقع داخل إطاره .In this research the differential cross section for elastic scattering of electron neutrino (or anti neutrino) on the electron was calculated within and outside the frame work of the Standard Model (SM) of elementary particle physics .The mathematical relation of deviation from this model was also calculated. This study showed that there is a deviation from the standard model of the order for the electron neutrino flavor. The reference [16] was not able to appear it quite clearly and independently, but It showed the deviation on average for all  flavors of neutrino together. Due to this  deviation is very small,  one can be neglected and therefore do not need to expand the framework of the standard model to include the electron neutrino mass, because in this case, it  is located inside its framework.